Potential distributions of Imperata cylindrica (L.) P. Beau under predicted climate change - Caballes, Samantha Alyssa C. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Climate change and biological invasions are threats to biodiversity. Climate change may increase the risk of biological invasions by altering environmental conditions and making them favorable for the spread of invasive species to their non-native ranges. Imperata cylindrica (cogon grass) is known to affect ecosystems, native biodiversity, and agriculture when introduced to a new range. Cogon grass can persist under climatic changes because of its tolerable and adaptable nature against a wide range of soil conditions, drought, and elevated atmospheric CO2 concentrations. In this study, I estimated the potential distribution of cogon grass under predicted climate change in the Philippines. Ecological niche modeling (ENM) using the Maximum Entropy (MaxEnt) algorithm was used to predict the potential distributions of cogon grass under present and future climate scenarios. A total of eight occurrence records and four environmental variables (mean temperature of wettest quarter, precipitation of driest quarter, total nitrogen, and pH(H2O)) were used to develop the model. The accuracy of the model was tested using threshold-independent (ROC and AUC) and -dependent (TSS) methods. The model has a mean AUC value of 0.534 from 8 replicate MaxEnt runs, which indicates a poor predictive performance and mean TSS value of 0.201, which indicates random accuracy. Future climate change scenarios (RCP 2.6, RCP 4.5, and RCP 8.5) of two global circulation models (BCC-CSM 1.1(m) and IPSL-CM5ALR) were used to forecast the climatic conditions in 2070. The Philippines was categorized to have a low habitat suitability for cogon grass by 2070 in all future scenarios, however, these predictions should be interpreted with caution considering the poor predictive performance of the model. The problems encountered in this study will be beneficial for future related studies in the Philippines. The findings of this study can guide environmental planners and managers in determining areas where reforestation or restoration efforts can be performed.